A network meta-analysis of therapies for hyperphosphatemia in CKD based on randomized trials - Congyang Zheng; Jia Liu; Tao Wang; Haiyang Hu; Yuanyuan Chen (Scientific Reports)
Abstract To update the efficacy and safety of different drugs for the treatment of patients with hyperphosphatemia in chronic kidney disease, we conducted a network meta-analysis of 22 therapies for the treatment of uncontrolled hyperphosphatemia in patients with chronic kidney disease (CKD). All randomized controlled trials on hyperphosphatemia published from January 2013 to November 2023 were searched from CNKI, VIP database, Wanfang database, PubMed, Scopus, and Cochrane databases. Meta-analysis was used to evaluate the serum phosphorus, calcium levels, total effective rate and adverse events of patients with chronic kidney disease (CKD). Data collection and quality evaluation were carried out by three evaluators, RevMan (5.5.3) and Stata (1.3.0). A total of 71 RCTs, and 22 treatment strategies were included in this NMA. The results showed that all treatment strategies were effective in improving patients’ blood phosphorus levels. Among them, SL + CT, CA + CC, SL and TCM had higher overall efficacy, RT, TCM and SL + CT had lower blood phosphorus levels, SL + CT, SL and NAM had lower blood calcium levels, and OAC, CC, NAM and SL had higher safety. Among them, SL + CT seems to be the most recommended treatment strategy. In addition, multidrug combination strategies usually have a higher efficacy and safety profile.